'10+3' Mechanism and its Development: A Comparative Analysis with the EU Experience - Wang, Genhua (Tufts Archival Research Center, 2007)
Submitted in partial fulfillment of the degree Master of Arts in Law and Diplomacy at the Fletcher School of Law and Diplomacy. Abstract: Compared with the high integration level of Europe Union, 10+3 mechanism is still in its very preliminary period of promoting East Asia regionalization; and it probably won't reach the level of EU in the foreseeable future, owing to different driving forces and constraints in the two regions. One of the major elements that guarantee EU achievement is said to be the homogeneity of democratic system in each member country, which 10+3 mechanism is going to lack for quite some time in the future. On the other hand, the willingness of promoting regionalization manifested by East Asia countries derives more from the desire for economic stability and continuing growth, in contrast with the longing for permanent security in West European countries in the early 50s. Different constraints and motivations determine the different path of integration in these two regions. With all the differences, there are some interesting similarities between the development of 10+3 and the early EU experience. To name only a few, 10+3 was born out of the East Asia financial crisis, while European integration came after the scourge of World War II; Before the initiation of Free Trade Agreements (FTA) were put on the table, there was an episode of Bilateral Monetary Swap Agreements in East Asia, in contrast with that of Coal and Steel Community in Europe before it started building a common market. Taking into account all the similarities and differences, a comparative analysis of these two integration processes might produce some useful findings for future development of 10+3 mechanism. This thesis, when combing the evolution and projecting the future of 10+3 process, tries to explore similarities and differences of these two integration process, for the purpose of extracting useful EU integration experiences while recognizing specific distinctions and constraints in East Asia. The thesis basically consists of four parts. The first part explores the genesis and evolution of 10+3 and theoretical diagnosis of its driving force. The second part addresses the two crucial steps of 10+3: the financial cooperation and the initiation of various FTAs across the region. The third part set forth the development of institution building, security cooperation in the framework. The fourth part argues that regional relations with United States will be indispensable in the future. The concluding part discusses various uncertainties on the development of 10+3.